Exploring the Link Between Intentional Self-Regulation and Hope in Thriving Among Salvadoran Adolescents Living in Poverty - Dennis, Julia. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Child Development.; Advisor: Richard Lerner.; Committee: Calvin Gidney, and Jonathan Tirrell.; Keyword: Developmental psychology.